An artistic solution to the problem of modern youth in the prose of A. Mizov - Khamisha T. Timizhev; Naima B. Bozieva (Кавказология)
This paper attempts to identify the aesthetic models of Kabardino-Circassian literature in its evolution, through the patterns of affirmation of ideals, stereotypes and cliches, appropriate for determining authors and specific time periods. The object of this study is the works of one of the brightest representatives of rural prose, a follower of the “writers of the sixties” Ahmed Mizov. The work focuses on identifying the peculiarities of the modern artist’s worldview, the connection of his works with life and a pronounced attitude to the reliability of the presentation. The relevance of the research topic is determined by its innovative nature associated with the analysis of unexplored works of Kabardino-Circassian literature. Researchers drew the following conclusions based on their scientific research of the prose writer's work: a) A. Mizov is a master of the short story; b) a sensitive perception of the surrounding world allowed the author to create a whole gallery of artistic images, memorable for their immediacy; c) significant changes in social and political life, in everyday life, in the psychology of the ethnic group over the past decades, the artistic need to understand and show them underlie the novels, short stories, short stories by Ahmed Mizov. He fills his novels, short stories, and short stories with an artistic vision of the world. Their heroes are lively, original people, young people, mostly rural and their problems. In the course of the study of the writer’s work, a set of scientific methods was applied, including comparative, comparative-historical, description and literary analysis, which, from the point of view of usage, makes it possible to determine both structural models and the content-conceptual aspect of the artist’s work. The practical significance of the article is the results obtained, which can become a theoretical aid in further research of the work of modern authors and in the study of Kabardino-Circassian literature. They can also be used to prepare undergraduate and graduate students in philological faculties, as well as lecture courses on linked peoples’ literature and Russian literature. The article is intended to facilitate the entry of works of national literature into the all-Russian cultural context.